Cryopreservation of DNA Origami Nanostructures. Issue 13 (4th March 2020) - Xin, Yang; Kielar, Charlotte; Zhu, Siqi; Sikeler, Christoph; Xu, Xiaodan; Möser, Christin; Grundmeier, Guido; Liedl, Tim; Heuer‐Jungemann, Amelie; Smith, David M.; Keller, Adrian
Abstract: Although DNA origami nanostructures have found their way into numerous fields of fundamental and applied research, they often suffer from rather limited stability when subjected to environments that differ from the employed assembly conditions, that is, suspended in Mg 2+ ‐containing buffer at moderate temperatures. Here, means for efficient cryopreservation of 2D and 3D DNA origami nanostructures and, in particular, the effect of repeated freezing and thawing cycles are investigated. It is found that, while the 2D DNA origami nanostructures maintain their structural integrity over at least 32 freeze–thaw cycles, ice crystal formation makes the DNA origami gradually more sensitive toward harsh sample treatment conditions. Whereas no freeze damage could be detected in 3D DNA origami nanostructures subjected to 32 freeze–thaw cycles, 1000 freeze–thaw cycles result in significant fragmentation. The cryoprotectants glycerol and trehalose are found to efficiently protect the DNA origami nanostructures against freeze damage at concentrations between 0.2 × 10 −3 and 200 × 10 −3 m and without any negative effects on DNA origami shape. This work thus provides a basis for the long‐term storage of DNA origami nanostructures, which is an important prerequisite for various technological and medical applications. Abstract : The stability of 2D and 3D DNA origami nanostructures subjected to repeated freeze–thaw cycles is investigated at both −20 and −196 °C. While being surprisingly stable under these conditions, ice crystal formation nevertheless gradually compromises the structural integrity of the DNA origami. Freeze damage can be suppressed by low concentrations of the cryoprotectants glycerol and trehalose.